The strategic leadership fundamentals for school - Mohd Ali, Hairuddin (IIUM Press, 2016)
This book contains ten chapters beginning with the theoretical foundation of strategic leadership in education. Entails to this, it is followed by nine more chapters (Strategic orientation, Strategic translation, Strategic alignment, Strategic intervention, Strategic competence, Restlessness, Absorptive capacity, Adaptive capacity and Wisdom) where each and every following chapters is representing the construct and variables which form the theoretical foundation and theoretical framework as been explained in the first chapter. This book is beneficial for postgraduate students who are specializing in Educational Management and Leadership.